Development of an Animated Video on Local Bogor Landforms to Enhance Understanding of IPAS Concepts - Tiara Rosalina; Rita Istiana; Yudhie Suchyadi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Learning Science and Social Studies, particularly the topic of landforms, remains challenging because classroom instruction is largely dependent on textbooks, limiting students' opportunities to experience meaningful and contextual learning. Since landform concepts are more easily understood when connected to the surrounding environment, this study aimed to develop an animated learning video based on the local environment of Bogor and examine its feasibility and effectiveness in improving students' conceptual understanding of IPAS. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The product was tested on 26 fifth-grade students. Data were collected through observations, interviews, expert validation sheets, teacher and student response questionnaires, and pretest and posttest assessments. Quantitative descriptive analysis was used to evaluate the product, while its effectiveness was determined using the N-Gain score. The results indicated that the animated video achieved excellent feasibility, with validation scores of 100% from media experts, 98% from subject matter experts, and 100% from language experts. Positive responses were also obtained from teachers (94.67%) and students (98%). Students' conceptual understanding improved, as reflected by the increase in the mean score from 61.54 on the pretest to 88.62 on the posttest, with an N-Gain score of 0.649, categorized as moderate. Therefore, the developed animated video is considered valid, practical, and effective as an alternative instructional medium for IPAS learning in elementary schools.